Strategi Promosi CV. Bilava Tour & Travel Pekanbaru dalam Meningkatkan Jumlah Penjualan Paket Tour Domestik - Rahma Putri Andita; Syaiful, Sefrona; Elwira Handayani; Febdarina, Sri; Lestari, Novia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the promotional strategy of CV. Bilava Tour & Travel Pekanbaru in increasing the number of domestic tour package sales and to determine the perception of guests (consumers) about the promotion of domestic tour packages at CV. Bilava Tour & Travel Pekanbaru. This research is located at CV. Bilava Tour & Travel Pekanbaru will be held from November 2023 to February 2024. This study uses a descriptive qualitative research type, with the population in this study being the staff at CV. Bilava Tour & Travel Pekanbaru and guests (consumers), and the research sample is 1 company leader, 1 promotion staff and 94 guests (consumers). The results of this study state that the promotional strategy of CV. Bilava Tour & Travel Pekanbaru in increasing the number of domestic tour package sales has been going well, namely the seven promotional mixes have been implemented, namely sales promotion, events and experiences, public relations and publicity, online marketing, mobile marketing, direct marketing, and personal sales. Guest (consumer) perceptions of domestic tour package promotions at CV. Bilava Tour & Travel Pekanbaru 4.10 is categorized as good to attract potential guests (consumers) to use the services of CV. Bilava Tour & Travel Pekanbaru.